Deteksi Bias Gender dan Domisili Menggunakan DIF (Differential Item Functioning): Analisis Instrumen Tes Keterampilan Pemecahan Masalah Terintegrasi Etnofisika - Nisa', Khoirun -; Suprapto, Nadi (Universitas Negeri Surabaya, 2023)
It is important for students to have problem-solving skills (PSS) when responding to the challenges of the 21st century. The Ministry of Education and Culture has developed an Kurikulum Merdeka that prioritizes cultural contexts. Local culture can be used in learning, especially in physics. Ethnophysics learning can increase students' KPM. However, previous researchers had not developed an ethnophysics-based PSS test instrument. This study analyzed the validity, reliability, and DIF (Differential Item Functioning) ethnophysics PSS test instruments using Rasch analysis. Rasch analysis includes analyses of validity, reliability, and DIF through Ministep software. The results of the Rasch analysis on the ethnophysics-based PSS test instrument showed the indicator items included in the valid and reliable categories. The DIF analysis of gender and domicile groups showed that one indicator out of 25 indicated bias. The probability of success for the group of male students is higher, and they benefit more from it than the female group. It's the same as the probability that a group of students living in village domiciles will benefit more than city domiciles.